Viral Replication Complexes: Structures, Functions, Applications and Inhibitors (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Viruses are obligate intracellular parasites that need to co-opt a living cell's machinery for replication. At the heart of the viral replication machinery are the nucleic acid polymerases, which are responsible for efficiently copying the viral genome. This process must often be coordinated with other viral processes including protein translation and viral packaging. The nucleic acid polymerases may also be responsible for generating genetic diversity that is important for escape from the host's defenses. The polymerases and other components of the replication machinery may serve as potential anti-viral targets. In this Special Issue, we seek to highlight recent advances into uncovering the structure and function of viral replication complexes. We are especially seeking to highlight the wide-range of methodologies used to gain structural insight into viral replication. Topics of interest include molecular mechanisms of nucleic acid polymerases, nucleic acid recognition and translocation, fidelity and error correction, interactions with lipid membranes, and coordination/regulation of transcription, translation and replication processes.